Sanksi Pidana Terhadap Tindak Pidana Pemalsuan Surat pada Data Polis Asuransi - I.G.A Bela Indah Komala Yusianadewi; I Nyoman Putu Budiartha; Made Minggu Widiantara (Fakultas Hukum Universitas Warmadewa, 2020)
Abstract—The crime of forgery of a letter is a criminal offence that resulted in the implication of truth and trust of the people. The offender wears a fake letter aims to gain an advantage for him. The crime of forgery of a letter that often occurs is the falsification of data insurance policy. An insurance policy is an agreement or insurance coverage is consensual (agreements), should be made in writing in a deed between the parties to the Treaty. As for the problem formulations used in this study are 1. How are the criminal sanctions arrangements for forgery of insurance policy data? 2. What is the legal responsibility of the insurance company for forgery of insurance policy data? this research using the normative legal research that aims to examine the legal certainty based on the result of the study of literature or the positive law in force. Legal materials collection technique begins by reading the law on counterfeiting a letter and by the method of record keeping. From the results of research and discussion of known forgeries of his own letters are listed in section 263 subsection (1) of the criminal code and section 263 subsection (2) of the criminal code which set about a criminal offence the use of fake letters, whereas the type of letter itself is regulated in article 264 of the criminal code and Act No. 40 of the year 2014 about perasuransian.